A combined treatment method for industrial wastewater
By combining the multiple core-shell structures of ozone catalysts and photocatalysts, efficient removal of oil pollution in petroleum industry wastewater is achieved, and the problem of low removal efficiency in the prior art is solved. The catalyst is easy to remove and the reaction is mild and pollution-free.
Patent Information
- Application Number
- CN202411800217.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The prior art is difficult to efficiently treat petroleum industry wastewater, especially in removing oil pollution.
Using a combined treatment method, ozone catalytic oxidation is performed first through an ozone catalyst, and then a photocatalyst is added to the naked liquid for photocatalytic oxidation. The ozone catalyst is spinel-type ferrite, and the photocatalyst has a multiple core-shell structure, including Fe3O4 microspheres, SiO2 layer, Ag layer and perovskite oxide.
In a short time, the catalyst is easily removed with a magnetic and easy to remove, and the reaction conditions are mild and there is no secondary pollution.
Smart Images

Figure CN119263463B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, in particular to a combined treatment method for industrial sewage. Background Art
[0002] If steel is the skeleton of the industrial body, then oil is the blood of the industrial body. Oil can not only be used as fuel, but also as the basic material for various chemical products. The large-scale development and application of oil has made great contributions to economic development. The oil industry can be roughly divided into three major departments: exploration, mining and refining. In the process of oil mining and refining, a large amount of oily wastewater will inevitably be produced. These wastewaters have a huge impact on the ecological environment and people's health. Therefore, it is very important to find a way to treat oil industry wastewater.
[0003] Photocatalytic technology is an emerging technology in recent years. It has great potential in the treatment of petroleum industry wastewater because of its advantages such as being able to utilize solar energy, mild reaction conditions, and no secondary pollution. Ozone oxidation is also a highly efficient technology for treating wastewater, and has a good treatment effect on some organic pollutants. If the two technologies are combined, the advantages of both technologies will inevitably improve the treatment efficiency of petroleum industry wastewater and improve the treatment effect. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a combined treatment method for industrial wastewater.
[0005] The technical solutions adopted are as follows:
[0006] A combined treatment method for industrial wastewater:
[0007] First, an ozone catalyst is added to the industrial wastewater, and ozone is continuously supplied for ozone catalytic oxidation, and the clear liquid is collected. Then, a photocatalyst is added to the clear liquid, and light is continuously supplied for photocatalytic oxidation treatment.
[0008] The ozone catalyst is spinel ferrite; the photocatalyst has a multiple core-shell structure, the photocatalyst has Fe3O4 microspheres as the core, and from the inside to the outside are SiO2 layer, Ag layer and perovskite oxide;
[0009] The spinel ferrite is Ln-doped zinc-manganese ferrite, where Ln is a lanthanide rare earth element;
[0010] The structural formula of the perovskite oxide is as follows:
[0011] Bi 0.5 Na 0.5 Ti 1-y (V 0.5 Sb 0.5 )y O3
[0012] Among them, 0<y≤0.1.
[0013] Furthermore, Ln is any one or more combinations of Nd, Eu, Gd, Tb, Dy, Yb, and Lu.
[0014] Furthermore, the structural formula of the Ln-doped zinc-manganese ferrite is Zn 0.5 Mn 0.5 Ln x Fe 2-x O4, 0<x≤0.1.
[0015] Furthermore, 0.07≤x≤0.09, and x is preferably 0.08.
[0016] Furthermore, the preparation method of the rare earth doped zinc manganese ferrite is as follows:
[0017] Dissolve zinc salt, iron salt, manganese salt and rare earth salt in deionized water to obtain a mixed solution, heat the mixed solution to 80-90°C, add sodium hydroxide solution dropwise thereto under stirring to make the pH of the system 10-11, stir and react for 1-5h after the dropwise addition, collect the precipitate, wash it thoroughly with deionized water and dry it, then place it in a muffle furnace and calcine it at 600-800°C for 1-5h and grind it.
[0018] Furthermore, 0.04≤y≤0.06, and y is preferably 0.05.
[0019] Furthermore, the preparation method of the photocatalyst is as follows:
[0020] Fe3O4 microspheres are added to a hydrochloric acid solution, and after ultrasonic oscillation treatment, they are taken out, washed with deionized water and anhydrous ethanol, and dried. Then, they are added to deionized water, anhydrous ethanol and ammonia water are added, and tetraethyl orthosilicate is added dropwise under stirring. After the dropwise addition, the mixture is sealed and stirred for reaction for 5-10 hours. After the stirring is completed, the supernatant is poured out, and the precipitate is washed with deionized water and anhydrous ethanol and dried to obtain a first intermediate. The first intermediate is subjected to amination treatment and then dispersed in a glutaraldehyde solution. After stirring for 1-5 hours, the mixture is washed with deionized water and anhydrous ethanol and dried. The mixture is then dispersed in ethanol, and a silver ammonia solution is added and stirred evenly. The obtained mixed solution is reacted in a 60-80°C water bath for 1-10 hours. The precipitate is collected, washed with deionized water and anhydrous ethanol, and dried to obtain a second intermediate. The second intermediate is immersed in a perovskite-type oxide precursor impregnation solution, taken out and dried, and finally heat-treated in a muffle furnace.
[0021] Furthermore, the heat treatment temperature is 600-800° C., and the heat treatment time is 1-5 h.
[0022] Furthermore, the amount of ozone catalyst is 0.1-1 g / L, and the amount of photocatalyst is 0.1-1 g / L.
[0023] Beneficial effects of the present invention:
[0024] The present invention provides a combined treatment method for industrial sewage, which achieves a removal efficiency of 99.9% for oil pollution in petroleum industrial sewage in a relatively short time through ozone catalytic oxidation combined with photocatalytic oxidation, and the catalysts are magnetic and easy to remove, the reaction conditions are mild, and there is no secondary pollution;
[0025] Spinel ferrite is a stable, fire-resistant and heat-resistant magnetic material. Many spinel ferrites have been used in the research of catalytic degradation of organic matter, but they are rarely used in ozone catalytic oxidation. There are also problems such as low catalytic performance. In order to improve the catalytic performance, lanthanide rare earth elements are used to dope it in this application. Since the rare earth ion radius is large, when the rare earth ion enters the B position (octahedral gap) in the ferrite lattice, it will cause lattice expansion, forming a distorted structure with abnormal valence and lattice defects, thereby improving the catalytic performance of ozone oxidation;
[0026] The photocatalyst in the present application has a multiple core-shell structure, with Fe3O4 microspheres as the core, and SiO2 layers, Ag layers and perovskite oxides from the inside to the outside. The core and shell of the multiple core-shell structure have three-dimensional contact, and the shells have three-dimensional contact, which can maximize the interface contact area of the heterojunction, help improve the charge transfer and separation efficiency, make it have high photocatalytic activity and have excellent treatment effect on petroleum industry wastewater;
[0027] Perovskite oxides have octahedral transport channels for carriers, and the interlayers can accommodate a large amount of organic and inorganic substances, so they have broad application prospects in photocatalysis. This application uses perovskite oxide as the outer shell layer, and the large contact area allows it to fully contact and react with petroleum industrial wastewater. The composite ion (V 0.5 Sb 0.5 ) 4+ Doping it is conducive to the formation of oxygen vacancies, which are the source of interface carriers and promote the improvement of the photocatalytic activity of the catalyst.
[0028] In the present application, the sol-gel method is used to prepare perovskite-type oxide as the outer shell layer to obtain a shell-shell structure with strong connection. The interaction force of the constructed materials is strong, the interface contact is relatively stable, and the shell thickness can be adjusted by changing the impregnation parameters. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a graph showing the change of oil removal rate over time in the combined treatment method for industrial wastewater in Example 1;
[0030] Figure 2 is a graph showing the change of oil removal rate over time in the combined treatment method for industrial wastewater in Example 2;
[0031] Figure 3 is a graph showing the change of oil removal rate over time in the combined treatment method for industrial wastewater in Example 3;
[0032] Figure 4 It is a curve chart showing the change of oil removal rate over time in the combined treatment method for industrial wastewater in Comparative Example 1;
[0033] Figure 5 It is a curve chart showing the change of oil removal rate over time in the combined treatment method for industrial wastewater in comparative example 2;
[0034] Figure 6 This is a curve chart showing the change of oil removal rate over time in the combined treatment method for industrial wastewater in comparative example 3. DETAILED DESCRIPTION
[0035] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0036] Embodiment 1:
[0037] A combined treatment method for industrial wastewater:
[0038] Add 4# fuel oil to deionized water to make a 1g / L solution to simulate industrial oily wastewater. Take 200ml of industrial oily wastewater, add 0.5g / L of ozone catalyst, then turn on the power of the ozone generator, pass ozone into the industrial oily wastewater at a rate of 1000mg / h, stir at 60rpm for 30min at room temperature, stop passing ozone and filter, add 0.5g / L of photocatalyst to the collected clear liquid, first adsorb in the dark for 30min, use a 300W xenon lamp with a 420nm filter to simulate the visible light source, the light source is 30cm away from the liquid surface of the industrial oily wastewater, stir continuously at 60rpm during the photocatalytic treatment, take 5ml of industrial oily wastewater as a sample with a pipette every 10min, measure the mass concentration of oil with an infrared spectrophotometer, and calculate the oil removal rate. The results are as follows: Figure 1 As shown, note: Figure 1 The horizontal axis 0min is approximately regarded as the oil removal rate after 30min of ozone catalytic oxidation;
[0039] Among them, the ozone catalyst is Zn 0.5 Mn0.5 Nd 0.08 Fe 1.92 O4, the specific preparation method is as follows:
[0040] Zinc nitrate hexahydrate, manganese nitrate hexahydrate, neodymium nitrate hexahydrate and ferric nitrate nonahydrate were weighed in a molar ratio of 0.5:0.5:0.08:1.92, and dissolved in 10 times the mass of deionized water to obtain a mixed solution, the mixed solution was heated to 80°C, and 1 mol / L sodium hydroxide solution was added dropwise under stirring to make the pH of the system 10, and the reaction was stirred for 5 hours after the dropwise addition, the precipitate was collected, washed thoroughly with deionized water and dried, and then calcined at 800°C for 2 hours in a muffle furnace and ground.
[0041] The photocatalyst has a multiple core-shell structure, wherein the photocatalyst has Fe3O4 microspheres as the core, and SiO2 layer, Ag layer and Bi layer from the inside to the outside. 0.5 Na 0.5 Ti 0.95 (V 0.5 Sb 0.5 ) 0.05 O3, the specific preparation method is as follows:
[0042] Weigh 13.5 g of ferric chloride and dissolve it in 400 ml of ethylene glycol. After stirring for 30 min, add 36 g of sodium acetate. Continue stirring for 2 h and then add 10 g of polyethylene glycol. Seal and heat to 180 °C for hydrothermal reaction for 24 h. After the hydrothermal reaction is completed, cool naturally to room temperature. Wash the precipitate with deionized water and anhydrous ethanol and dry it to obtain Fe3O4 microspheres. Add 0.4 g of Fe3O4 microspheres to 200 ml of 0.1mol / L hydrochloric acid solution, ultrasonic oscillation treatment for 30min, take out, wash with deionized water and anhydrous ethanol, dry, then add to 80ml deionized water, add 320ml anhydrous ethanol and 4ml ammonia water, add 0.6ml ethyl orthosilicate dropwise with a pipette under stirring, seal the reaction solution with plastic wrap after dropping, stir and react for 10h, pour out the supernatant after stirring, wash the collected precipitate with deionized water and anhydrous ethanol, dry the first intermediate, take 0.2g of the first intermediate and disperse it in 200ml of anhydrous The mixture was stirred at low speed for 2 h, and then filtered. The obtained solid was washed with deionized water and anhydrous ethanol and dried to obtain an amination first intermediate. The amination first intermediate was dispersed in 250 ml of glutaraldehyde solution (5%, diluted with 0.01 mol / L phosphate buffer), stirred at low speed for 3 h, and then filtered. The obtained solid was washed with deionized water and anhydrous ethanol and dried, and then dispersed in 200 ml of anhydrous ethanol. 20 ml of silver ammonia solution was added and the mixture was heated at 80 °C for 2 h. ℃ water bath environment for 5h, collect the product, wash with deionized water and anhydrous ethanol, and then dry to obtain the second intermediate; dissolve 50mmol sodium nitrate in 100ml deionized water to obtain liquid A, dissolve 50mmol bismuth nitrate pentahydrate in 100ml deionized water to obtain liquid B, dissolve 2.5mmol antimony trichloride in 20ml deionized water to obtain liquid C, dissolve 2.5mmol ammonium metavanadate in 20ml deionized water to obtain liquid D, drop 95mmol butyl titanate into 250ml anhydrous ethanol and add 5ml ethylene glycol ether ether to obtain liquid E, first mix liquid A, liquid B, liquid C and liquid D evenly, then add 45 ml of glacial acetic acid to obtain a mixed solution, keep the mixed solution stirring continuously, slowly drop liquid E into the mixed solution, continue to stir and react for 30 minutes after dropping, then stop stirring and place in a constant temperature water bath at 45°C for 30 minutes to obtain a perovskite oxide precursor impregnation solution, place the second intermediate in the perovskite oxide precursor impregnation solution for 10 minutes, take out, dry, transfer to a muffle furnace, heat to 800°C at a rate of 10°C / min, and keep warm for 2 hours.
[0043] Embodiment 2:
[0044] A combined treatment method for industrial wastewater:
[0045] Add 4# fuel oil to deionized water to make a 1g / L solution to simulate industrial oily wastewater. Take 200ml of industrial oily wastewater, add 0.5g / L of ozone catalyst, then turn on the power of the ozone generator, pass ozone into the industrial oily wastewater at a rate of 1000mg / h, stir at 60rpm for 30min at room temperature, stop passing ozone and filter, add 0.5g / L of photocatalyst to the collected clear liquid, first adsorb in the dark for 30min, use a 300W xenon lamp with a 420nm filter to simulate the visible light source, the light source is 30cm away from the liquid surface of the industrial oily wastewater, stir continuously at 60rpm during the photocatalytic treatment, take 5ml of industrial oily wastewater as a sample with a pipette every 10min, measure the mass concentration of oil with an infrared spectrophotometer, and calculate the oil removal rate. The results are as follows: Figure 2 As shown, note: Figure 2 The horizontal axis 0min is approximately regarded as the oil removal rate after 30min of ozone catalytic oxidation;
[0046] Among them, the ozone catalyst is Zn 0.5 Mn 0.5 Nd 0.08 Fe 1.92 O4, the specific preparation method is as follows:
[0047] Zinc nitrate hexahydrate, manganese nitrate hexahydrate, neodymium nitrate hexahydrate and ferric nitrate nonahydrate were weighed in a molar ratio of 0.5:0.5:0.08:1.92, and dissolved in 10 times the mass of deionized water to obtain a mixed solution, the mixed solution was heated to 80°C, and 1 mol / L sodium hydroxide solution was added dropwise under stirring to make the pH of the system 10, and the reaction was stirred for 5 hours after the dropwise addition, the precipitate was collected, washed thoroughly with deionized water and dried, and then calcined at 800°C for 2 hours in a muffle furnace and ground.
[0048] The photocatalyst has a multiple core-shell structure, wherein the photocatalyst has Fe3O4 microspheres as the core, and SiO2 layer, Ag layer and Bi layer from the inside to the outside. 0.5 Na 0.5 Ti 0.96 (V 0.5 Sb 0.5 ) 0.04 O3, the specific preparation method is as follows:
[0049] Weigh 13.5 g of ferric chloride and dissolve it in 400 ml of ethylene glycol. After stirring for 30 min, add 36 g of sodium acetate. Continue stirring for 2 h and then add 10 g of polyethylene glycol. Seal and heat to 180 °C for hydrothermal reaction for 24 h. After the hydrothermal reaction is completed, cool naturally to room temperature. Wash the precipitate with deionized water and anhydrous ethanol and dry it to obtain Fe3O4 microspheres. Add 0.4 g of Fe3O4 microspheres to 200 ml of 0.1mol / L hydrochloric acid solution, ultrasonic oscillation treatment for 30min, take out, wash with deionized water and anhydrous ethanol, dry, then add to 80ml deionized water, add 320ml anhydrous ethanol and 4ml ammonia water, add 0.6ml ethyl orthosilicate dropwise with a pipette under stirring, seal the reaction solution with plastic wrap after dropping, stir and react for 10h, pour out the supernatant after stirring, wash the collected precipitate with deionized water and anhydrous ethanol, dry the first intermediate, take 0.2g of the first intermediate and disperse it in 200ml The reaction mixture was added to anhydrous ethanol, and 50 ml of 10% APTES ethanol solution and 10 ml of deionized water were added, and the mixture was stirred at a low speed for 2 hours and filtered. The obtained solid was washed with deionized water and anhydrous ethanol and dried to obtain an amination first intermediate. The amination first intermediate was dispersed in 250 ml of glutaraldehyde solution (5%, diluted with 0.01 mol / L phosphate buffer), stirred at a low speed for 3 hours and filtered. The obtained solid was washed with deionized water and anhydrous ethanol and dried and then dispersed in 200 ml of anhydrous ethanol. 20 ml of silver ammonia solution was added. The reaction was carried out in a water bath at 80°C for 5 hours, the product was collected, washed with deionized water and anhydrous ethanol, and then dried to obtain a second intermediate; 50 mmol of sodium nitrate was dissolved in 100 ml of deionized water to obtain liquid A, 50 mmol of bismuth nitrate pentahydrate was dissolved in 100 ml of deionized water to obtain liquid B, 2 mmol of antimony trichloride was dissolved in 20 ml of deionized water to obtain liquid C, 2 mmol of ammonium metavanadate was dissolved in 20 ml of deionized water to obtain liquid D, 96 mmol of butyl titanate was dropped into 250 ml of anhydrous ethanol and 5 ml of ethylene glycol ethyl ether was added To obtain liquid E, first mix liquid A, liquid B, liquid C, and liquid D evenly, then add 45 ml of glacial acetic acid to obtain a mixed solution, keep the mixed solution stirring continuously, slowly drop liquid E into the mixed solution, continue stirring and react for 30 minutes after the dropping, then stop stirring and place in a 45°C constant temperature water bath for 30 minutes to obtain a perovskite oxide precursor impregnation solution, place the second intermediate in the perovskite oxide precursor impregnation solution for 10 minutes, take it out, dry it, transfer it to a muffle furnace, heat it to 800°C at a rate of 10°C / min, and keep it warm for 2 hours.
[0050] Embodiment 3:
[0051] A combined treatment method for industrial wastewater:
[0052] Add 4# fuel oil to deionized water to make a 1g / L solution to simulate industrial oily wastewater. Take 200ml of industrial oily wastewater, add 0.5g / L of ozone catalyst, then turn on the power of the ozone generator, pass ozone into the industrial oily wastewater at a rate of 1000mg / h, stir at 60rpm for 30min at room temperature, stop passing ozone and filter, add 0.5g / L of photocatalyst to the collected clear liquid, first adsorb in the dark for 30min, use a 300W xenon lamp with a 420nm filter to simulate the visible light source, the light source is 30cm away from the liquid surface of the industrial oily wastewater, stir continuously at 60rpm during the photocatalytic treatment, take 5ml of industrial oily wastewater as a sample with a pipette every 10min, measure the mass concentration of oil with an infrared spectrophotometer, and calculate the oil removal rate. The results are as follows: Figure 3 As shown, note: Figure 3 The horizontal axis 0min is approximately regarded as the oil removal rate after 30min of ozone catalytic oxidation;
[0053] Among them, the ozone catalyst is Zn 0.5 Mn 0.5 Nd 0.08 Fe 1.92 O4, the specific preparation method is as follows:
[0054] Zinc nitrate hexahydrate, manganese nitrate hexahydrate, neodymium nitrate hexahydrate and ferric nitrate nonahydrate were weighed in a molar ratio of 0.5:0.5:0.08:1.92, and dissolved in 10 times the mass of deionized water to obtain a mixed solution, the mixed solution was heated to 80°C, and 1 mol / L sodium hydroxide solution was added dropwise under stirring to make the pH of the system 10, and the reaction was stirred for 5 hours after the dropwise addition, the precipitate was collected, washed thoroughly with deionized water and dried, and then calcined at 800°C for 2 hours in a muffle furnace and ground.
[0055] The photocatalyst has a multiple core-shell structure, wherein the photocatalyst has Fe3O4 microspheres as the core, and SiO2 layer, Ag layer and Bi layer from the inside to the outside. 0.5 Na 0.5 Ti 0.94 (V 0.5 Sb 0.5 ) 0.06 O3, the specific preparation method is as follows:
[0056] Weigh 13.5 g of ferric chloride and dissolve it in 400 ml of ethylene glycol. After stirring for 30 min, add 36 g of sodium acetate. Continue stirring for 2 h and then add 10 g of polyethylene glycol. Seal and heat to 180 °C for hydrothermal reaction for 24 h. After the hydrothermal reaction is completed, cool naturally to room temperature. Wash the precipitate with deionized water and anhydrous ethanol and dry it to obtain Fe3O4 microspheres. Add 0.4 g of Fe3O4 microspheres to 200 ml of 0.1mol / L hydrochloric acid solution, ultrasonic oscillation treatment for 30min, take out, wash with deionized water and anhydrous ethanol, dry, then add to 80ml deionized water, add 320ml anhydrous ethanol and 4ml ammonia water, add 0.6ml ethyl orthosilicate dropwise with a pipette under stirring, seal the reaction solution with plastic wrap after dropping, stir and react for 10h, pour out the supernatant after stirring, wash the collected precipitate with deionized water and anhydrous ethanol, dry the first intermediate, take 0.2g of the first intermediate and disperse it in 200ml The reaction mixture was added to anhydrous ethanol, and 50 ml of 10% APTES ethanol solution and 10 ml of deionized water were added, and the mixture was stirred at a low speed for 2 hours and filtered. The obtained solid was washed with deionized water and anhydrous ethanol and dried to obtain an amination first intermediate. The amination first intermediate was dispersed in 250 ml of glutaraldehyde solution (5%, diluted with 0.01 mol / L phosphate buffer), stirred at a low speed for 3 hours and filtered. The obtained solid was washed with deionized water and anhydrous ethanol and dried and then dispersed in 200 ml of anhydrous ethanol. 20 ml of silver ammonia solution was added. The reaction was carried out in a water bath at 80°C for 5 hours, the product was collected, washed with deionized water and anhydrous ethanol, and then dried to obtain a second intermediate; 50 mmol of sodium nitrate was dissolved in 100 ml of deionized water to obtain liquid A, 50 mmol of bismuth nitrate pentahydrate was dissolved in 100 ml of deionized water to obtain liquid B, 3 mmol of antimony trichloride was dissolved in 20 ml of deionized water to obtain liquid C, 3 mmol of ammonium metavanadate was dissolved in 20 ml of deionized water to obtain liquid D, 94 mmol of butyl titanate was dropped into 250 ml of anhydrous ethanol and 5 ml of ethylene glycol ethyl ether was added To obtain liquid E, first mix liquid A, liquid B, liquid C, and liquid D evenly, then add 45 ml of glacial acetic acid to obtain a mixed solution, keep the mixed solution stirring continuously, slowly drop liquid E into the mixed solution, continue stirring and react for 30 minutes after the dropping, then stop stirring and place in a 45°C constant temperature water bath for 30 minutes to obtain a perovskite oxide precursor impregnation solution, place the second intermediate in the perovskite oxide precursor impregnation solution for 10 minutes, take it out, dry it, transfer it to a muffle furnace, heat it to 800°C at a rate of 10°C / min, and keep it warm for 2 hours.
[0057] Comparative Example 1:
[0058] The same as Example 1, except that the ozone catalyst is Zn 0.5 Mn 0.5Fe2O4, the specific preparation method is as follows:
[0059] Hexahydrated zinc nitrate, hexahydrated manganese nitrate and nonahydrated iron nitrate were weighed in a molar ratio of 0.5:0.5:2, and dissolved in 10 times the mass of deionized water to obtain a mixed solution. The mixed solution was heated to 80°C, and 1 mol / L sodium hydroxide solution was added dropwise under stirring to make the pH of the system 10. After the addition was completed, the reaction was stirred for 5 hours, and the precipitate was collected, washed thoroughly with deionized water, and dried. It was placed in a muffle furnace and calcined at 800°C for 2 hours and then ground. The treatment results are as follows: Figure 4 shown.
[0060] Comparative Example 2:
[0061] The method is basically the same as Example 1, except that the photocatalyst has a multiple core-shell structure. The photocatalyst has Fe3O4 microspheres as the core, and has SiO2 layers and Ag layers from the inside to the outside. The specific preparation method is as follows:
[0062] Weigh 13.5 g of ferric chloride and dissolve it in 400 ml of ethylene glycol. After stirring for 30 min, add 36 g of sodium acetate. Continue stirring for 2 h and then add 10 g of polyethylene glycol. Seal and heat to 180 °C for hydrothermal reaction for 24 h. After the hydrothermal reaction is completed, cool naturally to room temperature. Wash the precipitate with deionized water and anhydrous ethanol and dry it to obtain Fe3O4 microspheres. Add 0.4 g of Fe3O4 microspheres to 200 ml of 0.1mol / L hydrochloric acid solution, ultrasonic oscillation treatment for 30min, take out and wash with deionized water and anhydrous ethanol and dry, then add to 80ml deionized water, add 320ml anhydrous ethanol and 4ml ammonia water, add 0.6ml ethyl orthosilicate dropwise with a pipette under stirring, seal the reaction solution with plastic wrap after dropping, stir and react for 10h, pour out the supernatant after stirring, wash the collected precipitate with deionized water and anhydrous ethanol, dry the first intermediate, take 0.2g of the first intermediate and disperse it in 200ml anhydrous ethanol, and add AP with a mass concentration of 10% 50 ml of TES ethanol solution and 10 ml of deionized water were stirred at low speed for 2 hours and then filtered. The obtained solid was washed with deionized water and anhydrous ethanol and then dried to obtain the first amination intermediate. The first amination intermediate was dispersed in 250 ml of glutaraldehyde solution (5%, diluted with 0.01 mol / L phosphate buffer), stirred at low speed for 3 hours and then filtered. The obtained solid was washed with deionized water and anhydrous ethanol and then dried and dispersed in 200 ml of anhydrous ethanol. 20 ml of silver ammonia solution was added and reacted in a water bath environment at 80°C for 5 hours. The product was collected, washed with deionized water and anhydrous ethanol and then dried. The treatment results are shown in FIG. Figure 5 shown.
[0063] Comparative Example 3:
[0064] The same as Example 1, except that the photocatalyst has a multiple core-shell structure, wherein the photocatalyst has Fe3O4 microspheres as the core, and SiO2 layer, Ag layer and Bi layer from the inside to the outside. 0.5 Na 0.5 TiO3, the specific preparation method is as follows:
[0065] Weigh 13.5g of ferric chloride and dissolve it in 400ml of ethylene glycol. After stirring for 30min, add 36g of sodium acetate, continue stirring for 2h, then add 10g of polyethylene glycol, seal and heat to 180℃ for hydrothermal reaction for 24h. After the hydrothermal reaction is completed, cool naturally to room temperature, wash the obtained precipitate with deionized water and anhydrous ethanol and dry to obtain Fe3O4 microspheres, add 0.4g of Fe3O4 microspheres to 200ml of 0.1mol / L hydrochloric acid solution, treat with ultrasonic oscillation for 30min, take out, wash with deionized water and anhydrous ethanol and dry, then add to 80ml of deionized water, add 320ml of anhydrous ethanol and 4ml of ammonia water, add 0.6ml of tetraethyl orthosilicate dropwise with a pipette under stirring, seal the reaction solution with plastic wrap after dropping, stir and react for 10h, pour off the supernatant after stirring, wash the collected precipitate with deionized water and anhydrous ethanol and dry the first intermediate, take 0.2g The first intermediate was dispersed in 200 ml of anhydrous ethanol, and 50 ml of an APTES ethanol solution with a mass concentration of 10% and 10 ml of deionized water were added, and the mixture was stirred at a low speed for 2 hours and then filtered. The obtained solid was washed with deionized water and anhydrous ethanol and then dried to obtain an amination first intermediate. The amination first intermediate was dispersed in 250 ml of glutaraldehyde solution (5%, diluted with 0.01 mol / L phosphate buffer), stirred at a low speed for 3 hours and then filtered. The obtained solid was washed with deionized water and anhydrous ethanol and then dried. Disperse in 200 ml of anhydrous ethanol, add 20 ml of silver ammonia solution, react in a water bath at 80 ° C for 5 hours, collect the product, wash with deionized water and anhydrous ethanol, and then dry to obtain a second intermediate; dissolve 50 mmol of sodium nitrate in 100 ml of deionized water to obtain liquid A, dissolve 50 mmol of bismuth nitrate pentahydrate in 100 ml of deionized water to obtain liquid B, drop 100 mmol of butyl titanate into 250 ml of anhydrous ethanol and add 5 ml of ethylene glycol ether to obtain liquid C, first mix liquid A and liquid B After mixing evenly, add 45 ml of glacial acetic acid to obtain a mixed solution, keep the mixed solution stirring continuously, slowly drip liquid C into the mixed solution, continue stirring and react for 30 minutes after dripping, then stop stirring and place in a 45°C constant temperature water bath for 30 minutes to obtain a perovskite oxide precursor impregnation solution, place the second intermediate in the perovskite oxide precursor impregnation solution for 10 minutes, take out and dry, transfer to a muffle furnace and heat to 800°C at a rate of 10°C / min and keep warm for 2 hours. The treatment results are as follows: Figure 6 shown.
[0066] pass Figure 1-3 The comparison shows that different (V 0.5 Sb 0.5 ) 4+ Although the doping ratio will affect the catalytic degradation efficiency of industrial oily wastewater, the oil removal rate reached 99.9% after 60 min of photocatalysis;
[0067] pass Figure 1 and Figure 4 By comparison, it can be seen that rare earth ion doping can improve the efficiency of ozone catalytic oxidation by 25%;
[0068] pass Figure 1 and Figure 5 By comparison, it can be seen that when Bi is not included 0.5 Na 0.5 Ti 0.94 (V 0.5 Sb 0.5 ) 0.06 When O3 was the outermost layer, the oil removal rate decreased from 99.9% to 94.6% after 60 min of photocatalysis;
[0069] pass Figure 1 and Figure 6 By comparison, we can see that (V 0.5 Sb 0.5 ) 4+ Doping plays a positive role in improving the photocatalytic oxidation effect.
[0070] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A combined treatment method for industrial wastewater, characterized in that: First, an ozone catalyst is added to the industrial wastewater, and ozone is continuously supplied for ozone catalytic oxidation, and the clear liquid is collected. Then, a photocatalyst is added to the clear liquid, and light is continuously supplied for photocatalytic oxidation treatment. The ozone catalyst is spinel ferrite; the photocatalyst has a multiple core-shell structure, the photocatalyst has Fe3O4 microspheres as the core, and from the inside to the outside are SiO2 layer, Ag layer and perovskite oxide; The spinel ferrite is Ln-doped zinc-manganese ferrite, where Ln is a lanthanide rare earth element; The structural formula of the perovskite oxide is as follows: Bi 0.5 Na 0.5 You 1-y (V 0.5 Sb 0.5 ) y O3 Among them, 0<y≤0.
1.
2. The combined treatment method for industrial wastewater according to claim 1, characterized in that: Ln is any one or more combinations of Nd, Eu, Gd, Tb, Dy, Yb, and Lu.
3. The combined treatment method for industrial wastewater according to claim 1, characterized in that: The structural formula of the Ln-doped zinc-manganese ferrite is Zn 0.5 Mn 0.5 Ln x Fe 2-x O4, 0<x≤0.
1.
4. The combined treatment method for industrial wastewater according to claim 3, characterized in that: The preparation method of the Ln-doped zinc-manganese ferrite is as follows: Dissolve zinc salt, iron salt, manganese salt and rare earth salt in deionized water to obtain a mixed solution, heat the mixed solution to 80-90°C, add sodium hydroxide solution dropwise thereto under stirring to make the pH of the system 10-11, stir and react for 1-5h after the dropwise addition, collect the precipitate, wash it thoroughly with deionized water and dry it, then place it in a muffle furnace and calcine it at 600-800°C for 1-5h and grind it.
5. The combined treatment method for industrial wastewater according to claim 1, characterized in that: 0.04≤y≤0.06。 6. The combined treatment method for industrial wastewater according to claim 1, characterized in that: The preparation method of the photocatalyst is as follows: Fe3O4 microspheres are added to a hydrochloric acid solution, and after ultrasonic oscillation treatment, they are taken out, washed with deionized water and anhydrous ethanol, and dried. Then, they are added to deionized water, anhydrous ethanol and ammonia water are added, and tetraethyl orthosilicate is added dropwise under stirring. After the dropwise addition, the mixture is sealed and stirred for reaction for 5-10 hours. After the stirring is completed, the supernatant is poured out, and the precipitate is washed with deionized water and anhydrous ethanol and dried to obtain a first intermediate. The first intermediate is subjected to amination treatment and then dispersed in a glutaraldehyde solution. After stirring for 1-5 hours, the mixture is washed with deionized water and anhydrous ethanol and dried. The mixture is then dispersed in ethanol, and a silver ammonia solution is added and stirred evenly. The obtained mixed solution is reacted in a 60-80°C water bath for 1-10 hours. The precipitate is collected, washed with deionized water and anhydrous ethanol, and dried to obtain a second intermediate. The second intermediate is immersed in a perovskite-type oxide precursor impregnation solution, taken out and dried, and finally heat-treated in a muffle furnace.
7. The combined treatment method for industrial wastewater according to claim 6, characterized in that: The heat treatment temperature is 600-800°C, and the heat treatment time is 1-5h.
8. The combined treatment method for industrial wastewater according to claim 1, characterized in that: The dosage of ozone catalyst is 0.1-1g / L, and the dosage of photocatalyst is 0.1-1g / L.
Citation Information
Patent Citations
Rare earth-based halide perovskite material and preparation method and application thereof
CN111453758A
Porous magnetic conductive copper self-doped copper zinc ferrite catalyst as well as preparation method and application thereof
CN113332988A